PARTISIPASI PEREMPUAN DALAM DUNIA PARIWISATA - Haslinda Haslinda (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
Many women workers engaged in various activities in the tourism sector, but gender issues are always attached to them which limit womens’ activities in the public domain such as various forms of marginalization, discrimination, and subordination that was reflected in the inequality of wages or salaries. Dual role for women workers into a dilemma, on one hand they are as housewives who have excellent troubleshooting and households, on the other hand they must be professional in a career.